Therapeutic anti-cancer vaccines: a systematic review of prospective intervention trials for common hematological malignanciesResearch in context - Darshi Shah; Veer Shah; Karan Shah; Prachi J. Shah; Muatassem Alsadhan; Alyson Haslam; Vinay Prasad; Muzaffar H. Qazilbash; Rajshekhar Chakraborty; Ghulam Rehman Mohyuddin (EClinicalMedicine, 2025)
Summary: Background: This review comprehensively assesses all prospective trials on anti-cancer vaccines for common hematological malignancies by analyzing trial designs, endpoints, and whether these endpoints are met across these trials. Methods: We included onco prospective clinical trials involving therapeutic anti-cancer vaccines for hematological malignancies published up to May 2025. We excluded retrospective cohort studies, case reports, non-research opinion publications, and studies not related to hematological malignancies. Information sources: Embase, MEDLINE, Web of Science Core Collection, and ClinicalTrials.gov. All the included RCTs were assessed for bias using the Cochrane Handbook for Systematic Review of Interventions, version 6.2 and Cochrane risk-of-bias tool. Results were synthesized descriptively, using frequencies (%) and medians (interquartile range [IQR]). The study protocol utilized was recorded in the PROSPERO database (Registration ID. CRD42024504780). Findings: Out of 2856 studies screened, a total of 187 studies were included. The median sample size was 18 (IQR = 20), and 33/187 (18%) studies were randomized. Most utilized primary endpoints were translational and safety, of which the endpoint was met 65/81 (80%) and 51/74 (69%) of the time, respectively. In 35/187 (19%) of the total studies included, the primary endpoint was a clinical efficacy endpoint (PFS, OS, duration of remission, cancer response) of which, 11/35 (31%) of studies met their clinical primary endpoint. Of the 33 randomized studies, 24 measured a clinical endpoint as their primary endpoint. Besides BCG administration in AML, no vaccine trial met a clinical efficacy endpoint in a randomized trial. There was not a single instance in which a vaccine product demonstrated an improvement in overall survival. The risk of bias assessment for RCTs showed most studies at low or intermediate risk of bias. Interpretation: This systematic review of all therapeutic anti-cancer vaccine trials in common hematological malignancies shows that although vaccines generally demonstrate immunogenicity, they have mostly failed to show consistent anti-cancer activity. Limitations include a lack of quantitative synthesis due to heterogeneity of assessed interventions, small sample sizes in most studies, and a lack of clear endpoint description in some studies. Funding: None. PROSPERO Registration ID. CRD42024504780.